Disrupting disruptions: enhancing supply chain resilience—lessons from the US Air Force - Ron Berger; Ralf Wagner; Paul M. Dion; Olga Matthias (Annals of Operations Research, 2025)
Black swan events have highlighted the importance of supply chain resilience and hence drawn increased attention from academia. Using military supply chains as our research setting, we illustrate how supply chain resilience can be implemented in civilian networks and incorporate agility and flexibility into a responsive system-to-system model. We use a simulation model based on the Cassandra application to further develop supply chain network resilience theory. Our model provides updated situational awareness to decision makers and allows managers to identify direct and indirect threats to supply chains, allowing adaptation to unforeseen situations. We developed a dynamic, whole-system network model to provide timely, accurate, updateable and scalable information to planners and decision-makers at all levels in-order to reduce risk and increase resilience.
Keywords: 000; Supply chain resilience; Complex adaptive systems; Casandra; Modeling; Disruption